THE ECO ENZYME APPLICATION ON INDUSTRIAL WASTE ACTIVATED SLUDGE DEGRADATION - Temmy Wikaningrum; Rijal Hakiki; Maryani Paramita Astuti; Yunita Ismail; Filson Maratur Sidjabat (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2022)
Aim: This study aims to determine whether the application of eco enzyme affects the industrial waste activated sludge degradation and to compare the effects of eco enzyme made from oranges and tomatoes. Methodology and results: The experiments were done on the laboratory scale for 12 days by applying 10% of eco enzyme in the sludge samples. It showed both tomatoes and oranges eco enzymes can decrease the pH from 6.9 to 4.7 compared to control which was stable at 6.9. The reduction of COD, TSS, and VSS by tomato eco enzyme applications were 61%, 39% 41% respectively compared to by orange eco enzyme application that showed a higher reduction of 78%, 45%, 46% respectively. The control samples also show the reduction of COD, TSS, and VSS by 21%, 23%, 30% respectively. The reduction of organic content in the control samples of sludge (8.9%) was higher than the samples with eco enzyme (3.5%). Conclusion, significance, and impact study: The results showed that eco enzyme application significant statistically affected reduction of pH, COD, organic content, but not significant statistically on TSS and VSS reductions. Comparing the application of orange and tomatoes eco enzyme did not show the significant different treatment.